Study of the metabolome and muscle strength measures for the characterization of patients with myotonic dystrophy type 1 - Mateus, Tiago Duarte Cordeiro (2023)
Myotonic dystrophy type 1 (DM1) is an autosomal dominant hereditary disease caused by an alteration leading to an abnormal expansion of unstable repetitions of CTG in the 3’ untranslated region of Myotonic Dystrophy Protein Kinase (DMPK) gene. DM1 is characterized by myotonia, progressive distal muscle weakness and by multisystemic involvement namely cataracts, muscle pain, cardiac and respiratory dysfunctions, endocrine dysfunctions (insulin resistance, metabolic syndrome, dyslipidemia), cancer and alterations in the central nervous system (CNS). Patients with DM1 have a frequency of metabolic syndrome higher than in the general population. Thus, the study of the metabolome is of a great importance since it can give new insight regarding the molecular pathways affected in DM1 diseases as well as to discriminate between the different degrees of severities in patients with DM1 and may also, lead to the development of new metabolic therapeutics. Given the previously reported metabolic alterations observed in patients DM1, we considered that the evaluation of the metabolic profile of those patients of paramount importance. Therefore, we started with the literature review for summarizing the metabolic alterations previously reported in patients with DM1 and the relationship of Lipin with the metabolic alterations in DM1 (Chapter I). Essentially, the previous studies showed a clear metabolic alteration between patients with DM1 and control groups, namely, increased total cholestrol, Low-density lipoprotein, triacylglycerol, insulin and HOMA-Insulin resistance levels, increased glucose levels and low levels of high-density lipoprotein. This review also showed a potential relationship between Lipin and its association with metabolic abnormalities found in patients with DM1, namely, the metabolic roles in adipose tissue, skeletal-muscle, liver and its association with dyslipidemia and insulin resistance, which is a characteristic feature in patients with DM1. The metabolic profile of patients with DM1 then was evaluated using the ATR-FTIR spectroscopy technique, together with multivariate analysis, which is suitable for providing a (bio)chemical profile of patients with DM1 and controls. Essentially, DM1-derived fibroblast and controls were used, and the results showed a clear discrimination within DM1-derived fibroblast with different CTG repeat length and age at onset, meaning that they may have a distinct metabolic profile. This discrimination can be attributed mainly to the altered lipid metabolism in 1800-1500 region cm-1 . It was also possible to discriminate between the control groups and both DM1-derived fibroblast from Coriell institute and Centro Hospitalar do Tâmega e Sousa in 3000-2800 cm-1 region (Chapter II). Additionally, a systematic review was made to gather information of all outcome and measurements used to assess muscle strength in adult patients with DM1 (Chapter IV). The cardiac, skeletal and respiratory muscle strength was evaluated. Briefly, the systematic review showed a consistent use of echocardiography, quantitative muscle test, manual muscle test and manometry to assess cardiac, skeletal and respiratory muscle strength. The measures of choice to assess muscle strength were: (1) ejection fraction in cardiac muscle; (2) muscle isometric torque, grip strength and medical research council (0-5 points and 0-60 points) in skeletal-muscle; (3) maximal inspiratory pressure and maximal expiratory pressure in respiratory muscles. In conclusion, our results suggest that there is a need to further research the lipid metabolism of patients with DM1, not only to better characterize these patients but also to understander the underlying mechanism of lipid abnormalities and to have new insights of Lipin in DM1. FTIR spectroscopy is a valuable tool to characterize patients with DM1 severities, which is crucial for a proper diagnosis and further studies. We successfully gather the more consensual and important measures to evaluate muscle strength. The results obtained were important and useful given that they will be valuable for muscle strength evaluation in future clinical trials and observational studies, particularly to test if a drug is improving muscle strength in patients with DM1.